Night-time blood pressure load is associated with higher left ventricular mass index in renal transplant recipients - KOÇ, MEHMET (NATURE PUBLISHING GROUP, 2003)
The absence of nocturnal fall in blood pressure (BP) is named as nondipper status, which has been shown to be an additional risk factor for the development of left ventricular hypertrophy and cardiovascular events in several high-risk groups. The aim of this study was to determine the influences of the nondipper status and nocturnal blood pressure loads on left ventricular mass index (LVMI) in renal transplant recipients. A total of 35 nondiabetic renal transplant recipients were included into the study. A 24-h ambulatory blood pressure monitoring (ABPM) was performed for all recipients. The nondipper status was defined as either an increase in night-time mean arterial pressure (MAP) or a decrease of no more than 10% of daytime MAP. LVMI was measured by using two-dimensional guided M-mode echocardiography. The night-time systolic blood pressure (SBP) load was defined as the percentage of the time, during which SBP exceeded 125 mmHg during night time. The nondipping was common among renal transplant recipients, of whom 60% were nondipper in our study. LVMI was significantly higher in the nondipper group vs the dipper group (133 +/- 35 g/m(2) VS 109 +/- 26 g/m(2), P= 0.04). A fall in MAP at night time was 14.5 +/- 4.3% in the dipper group, while it was 1.4 +/- 6.1% in the nondipper group (P< 0.001). On stepwise multiple regression analysis, night-time SBP load and haemoglobin were independent predictors of LVMI (R-2 = 0.53). In conclusion, nondipping is common after renal transplantation. Night-time SBP load and low haemoglobin are closely related to the increase in LVMI in renal transplant recipients. ABPM may be a more useful tool in optimizing treatment strategies to reduce cardiovascular events in renal transplant recipients.
Keywords: kidney transplantation; left ventricular hypertrophy; ambulatory blood pressure monitoring; ESSENTIAL-HYPERTENSION; WALL THICKNESS; CARDIOMYOPATHY; DISEASE; HYPERTROPHY; BORDERLINE; MORBIDITY; MORTALITY; DIPPERS; IMPACT